Menanamkan Nilai Keteladanan Dalam Pembelajaran SKI Melalui Kartu Role Play - Ubaidillah Al Azhari, Muh. (Maliki Interdisciplinary Journal, 2025)
The teaching of Islamic Cultural History (SKI) not only aims to convey knowledge about historical events but also plays an important role in instilling exemplary values from Islamic figures. Values such as honesty, courage, patience, and the spirit of struggle are part of noble character traits that must be instilled in students. However, in practice, SKI learning often relies on lecture methods that tend to be one-way and lack active student involvement. This article aims to examine the effectiveness of using role play card media as a participatory learning strategy to instill exemplary values in SKI lessons, with examples such as the stories of Prophet Ibrahim and Prophet Ismail, the steadfastness of the Prophet’s preaching in Thaif, and the steadfast faith of Bilal bin Rabah. The research method used is a qualitative approach with a library research type. Data were collected from various literature sources such as books, scientific journals, and relevant articles. The study results show that role play card media can create an interactive and contextual learning environment, making it easier for students to internalize and practice exemplary values more deeply. Thus, this strategy can be an effective alternative in supporting character building through the SKI subject.